An Eimeria maxima Antigen: Its Functions on Stimulating Th1 Cytokines and Protective Efficacy Against Coccidiosis - Chen, Chen; Zhang, Yue; Liu, Jianhua; Wang, Mingyue; Lu, Mingmin; Xu, Lixin; Yan, Ruofeng; Li, Xiangrui; Song, Xiaokai (Frontiers in Immunology, 2022)
A consensus is that the Th1 immune response plays a predominant role against avian coccidiosis. Therefore, an antigen with the ability to induce Th1 cytokine responses is an ideal candidate for the development of coccidiosis vaccines. In our previous study, EmARM-β, a Th1 cytokines-stimulating antigen, was screened from the cDNA expression library of Eimeria maxima (E. maxima). Herein, we verified its stimulative effects on Th1 cytokine productions and evaluated its protective efficacy against E. maxima infection. Recombinant EmARM-β protein was expressed, and eukaryotic expression plasmid pVAX1-EmARM-β was also constructed for the immunization of birds. An immunofluorescence assay was performed to detect the native form of EmARM-β protein in the stage of sporozoites. Expressions of specific transcription factors and cytokines in immunized chickens were measured using qPCR and ELISA to verify its stimulating function on Th1 cytokines. Specific IgG antibody levels and T lymphocyte subpopulation in the immunized chickens were detected using ELISA and indirect flow cytometry to determine induced immune responses. The results showed that EmARM-β native protein is massively expressed in the sporozoites stage of E. maxima. Effective stimulation from the EmARM-β antigen to T-bet and Th1 cytokines (IL-2 and IFN-γ) was observed in vivo. After being immunized with rEmARM-β or pVAX1-EmARM-β, significant promotion to the proportion of CD4+ and CD8+ T cells and the level of antigen-specific IgG antibodies in immunized chickens was also observed. Furthermore, vaccination with rEmARM-β antigen or pVAX1-EmARM-β resulted in alleviated weight loss and enteric lesion, reduced oocyst output, and higher anticoccidial index (ACI) in challenged birds. These results indicate that EmARM-β antigen can effectively stimulate the expression of Th1 cytokines and initiate host immune responses, providing moderate protective efficacy against E. maxima. Notably, EmARM-β protein is a promising candidate for developing a novel anticoccidial vaccine.